A detailed lipidomic study of human pathogenic fungi Candida auris. Issue 6 (5th August 2020) - Shahi, Garima; Kumar, Mohit; Kumari, Sonam; Rudramurthy, Shivaprakash M; Chakrabarti, Arunaloke; Gaur, Naseem A; Singh, Ashutosh; Prasad, Rajendra
ABSTRACT: The present study is an attempt to determine the lipid composition of Candida auris and to highlight if the changes in lipids can be correlated to high drug resistance encountered in C. auris . For this, the comparative lipidomics landscape between drug-susceptible (CBS10913T) and a resistant hospital isolate (NCCPF_470033) of C. auris was determined by employing high throughput mass spectrometry. All major groups of phosphoglycerides (PGL), sphingolipids, sterols, diacylglycerols (DAG) and triacylglycerols (TAG), were quantitated along with their molecular lipid species. Our analyses highlighted several key changes where the NCCPF_470033 showed an increase in PGL content, specifically phosphatidylcholine, phosphatidylglycerol, phosphatidylserine, phosphatidylinositol, and phosphatidylethanolamine; odd chain containing lipids and accumulation of 16:1-DAG and 16:0-DAG; depletion of 18:1-TAG and 18:0-TAG. The landscape of molecular species displayed a distinct imprint between isolates. For example, the levels of unsaturated PGLs, contributed by both odd and even-chain fatty acyls were higher in resistant NCCPF_470033 isolate, resulting in a higher unsaturation index. Notwithstanding, several commonalities of lipid compositional changes between resistant C. auris and other Candida spp., the study could also identify distinguishable changes in specific lipid species in C. auris . Together, the data highlights the modulation of membrane lipid homeostasis associated with drug-resistant phenotype of C. auris . Abstract : The present study determines the lipid composition of Candida auris and highlights alterations in lipids that may be correlated to high drug resistance in fungi.